Genetic analysis for designing an ideotype of high-yielding sorghum based on existing lines performance - Desta Wirnas; Neni Oktanti; Hana Nur Rahmi; DEWI ANDRIANI; Faturrahman FATURRAHMAN; ERIN PUSPITA RINI; Siti Marwiyah; Trikoesoemaningtyas TRIKOESOEMANINGTYAS; DIDY SOPANDIE (Society for Indonesian Biodiversity, 2021)
Abstract. Wirnas D, Oktanti N, Rahmi HN, Andriani D, Faturrahman, Rini EP, Marwiyah S, Trikoesoemaningtyas, Sopandie D. 2021. Genetic analysis for designing an ideotype of high-yielding sorghum based on existing lines performance. Biodiversitas 22: 5286-5292. Sorghum is a potential crop as an alternative and substitutes food source for rice or wheat. The ideal type of sorghum design for a high-yielding trait is needed to streamline the process of selecting the best genotype that can be developed into pure lines and released as varieties. The research purpose was to design the ideal type of sorghum based on the morphological, physiological, and agronomic characters that contribute to a high-yielding trait. The research was carried out at the Agriculture Research Center for Biotechnology and Genetic Resources, Bogor, West Java, Indonesia and experimental field of IPB University, Bogor, Indonesia. The genetic materials used in this study consisted of 56 F5 sorghum lines advanced from three segregating populations and 8 check varieties. The ideal type of sorghum to obtain a genotype with high grain weight per panicle was to have a phenotypic value of 150-235 cm for plant height (medium plant height). The physiological and agronomic characters obtained to design the ideal type of sorghum were stem diameter, leaf number, flag leaf area, leaf greenness, green leaf percentage, and panicle diameter with the minimum value for the traits are 17 mm, 10, 209 cm2, 44 CCI units, 48%, and 49 mm, respectively. This ideotype is going to be used as selection criteria for selection of high-yielding sorghum genotypes.